Prediction of a High Temperature Bonding Condition at the Interface for the Hot-Rolled Stainless Steel Clad Plate on Rolling - Guan, B.; Chen, B.Y.; Zang, Y.; Qin, Q. (Проблемы прочности, 2018)
The stainless steel-carbon steel clad plate was investigated using the theoretical analysis of various factors influencing the high-temperature interfacial bonding during its rolling. Phenomenological prediction analysis model of interfacial bonding strength at high temperature which considers the vacuum depth, rolling temperature, and rolling reduction, was established. The specific thermal simulation experiment was designed, the bonding strength of carbon steel and stainless steel at 1000~1200°C and compression degree of 10~30% was measured by a Gleeble 3500 thermal simulator, as a result, the interfacial bonding ratio was obtained. The results show that the bonding ratio is 0.5-0.65 at the experimental temperature and compression degree. The numerical simulation method was used to analyze the influence of the compression degree of the first pass for a 2000×1500×100 mm stainless steel clad plate under the interfacial bonding condition. The simulation results show that the optimum compression degree of the first pass is 15-20% at the rolling temperature of 1200°C.